2019
DOI: 10.1038/s41380-019-0585-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective biomarkers of major depressive disorder: a systematic review and meta-analysis

Abstract: Leading biological hypotheses propose that biological changes may underlie major depressive disorder onset and relapse/recurrence. Here, we investigate if there is prospective evidence for biomarkers derived from leading theories. We focus on neuroimaging, gastrointestinal factors, immunology, neurotrophic factors, neurotransmitters, hormones, and oxidative stress. Searches were performed in Pubmed, Embase and PsychInfo for articles published up to 06/2019. References and citations of included articles were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
197
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(204 citation statements)
references
References 114 publications
4
197
1
2
Order By: Relevance
“…Depression is significantly under-reported, under-diagnosed, and under-treated, in part due to its heterogeneous nature which involves subjective and culturally shaped experiences such as motivation, mood, and well-being 3 . Furthermore, in spite of its prevalence, the dynamics of its onset and development remain poorly understood 4 6 , limiting the development of treatment options 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Depression is significantly under-reported, under-diagnosed, and under-treated, in part due to its heterogeneous nature which involves subjective and culturally shaped experiences such as motivation, mood, and well-being 3 . Furthermore, in spite of its prevalence, the dynamics of its onset and development remain poorly understood 4 6 , limiting the development of treatment options 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this shortcoming, either examining a biological panel of several markers [ 88 ] or phenotyping MDD and TRD into distinct subtypes could be considered. However, a recent meta-analysis showed that only cortisol has a predictive effect on onset/relapse and recurrence of MDD making the integration of biomarkers for personalizing TRD treatment a futuristic milestone yet to be discovered [ 89 ].…”
Section: Towards a More Personalized Dbs Treatment Approach For Trmentioning
confidence: 99%
“…Táto sieť spravidla zahŕňa manifestované prejavy psychickej poruchy (symptómy), no taktiež môže a mala by zahŕňať aj ďalšie externé faktory, ak tieto sú príčinou vzťahov medzi pozorovanými symptómami (Pearl, 2000) alebo prispievajú k celkovej reziliencii, prípadne vulnerabilite. Psychická porucha ako napríklad depresia tak nie je výhradne biologickou poruchou (Kennis et al, 2019), ktorá by mala byť entitou lokalizovanou výlučne v mozgu človeka (de Kovel et al, 2019) alebo alebo poruchou so silným genetickým základom (Border et al, 2019). Etiológia depresie totiž zahŕňa komplexnú interakciu človeka s jeho prostredím (Clark & Chalmers, 1998) Vnímanie povahy psychopatológie na strane klinického psychológa, psychiatra, či psychoterapeuta so sebou zároveň nesie špecifickú interpretáciu povahy a príčin utrpenia na strane pacienta.…”
Section: Intervencia a Komorbidita V Sieťovom Prístupeunclassified